2015
DOI: 10.1038/ncomms10169
|View full text |Cite
|
Sign up to set email alerts
|

Multitrophic diversity in a biodiverse forest is highly nonlinear across spatial scales

Abstract: Subtropical and tropical forests are biodiversity hotspots, and untangling the spatial scaling of their diversity is fundamental for understanding global species richness and conserving biodiversity essential to human well-being. However, scale-dependent diversity distributions among coexisting taxa remain poorly understood for heterogeneous environments in biodiverse regions. We show that diversity relations among 43 taxa—including plants, arthropods and microorganisms—in a mountainous subtropical forest are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 64 publications
3
61
0
2
Order By: Relevance
“…We integrated published HTS molecular datasets for soil (Schuldt et al, ) and deadwood (Purahong et al, ) fungal communities derived from 27 comparative study plots (30 m × 30 m) located in the Gutianshan National Nature Reserve (GNNR, 81 km 2 , 29°08′–29°17′N, 118°27′–118°11′E), Zhejiang province, South‐East China, as part of the Biodiversity‐Ecosystem Functioning (BEF‐China) project (Bruelheide et al, ). The vegetation here is characterized as moist, mixed subtropical broadleaved forest with successional ages ranging from <20 to ≥80 years (Bruelheide et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We integrated published HTS molecular datasets for soil (Schuldt et al, ) and deadwood (Purahong et al, ) fungal communities derived from 27 comparative study plots (30 m × 30 m) located in the Gutianshan National Nature Reserve (GNNR, 81 km 2 , 29°08′–29°17′N, 118°27′–118°11′E), Zhejiang province, South‐East China, as part of the Biodiversity‐Ecosystem Functioning (BEF‐China) project (Bruelheide et al, ). The vegetation here is characterized as moist, mixed subtropical broadleaved forest with successional ages ranging from <20 to ≥80 years (Bruelheide et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For both sets of material, we used the same primer pairs (ITS1F [5′‐C​T​T​G​G​T​C​A​T​T​T​A​G​A​G​G​A​A​G​T​A​A​‐3′] and ITS4 [5′‐T​C​C​T​C​C​G​C​T​T​A​T​T​G​A​T​A​T​G​C​‐3′]) to amplify the entire fungal internal transcribed spacer (ITS) rRNA region (Gardes & Bruns, ; White, Bruns, Lee, & Taylor, ). The amplified fragments were then subjected to 454 pyrosequencing and bioinformatics analysis as described in detail by Purahong, Wubet, et al (), Purahong et al () and Schuldt et al (). We did a unidirectional sequencing of the amplicons from the ITS4 end (reverse primer), thus the fungal ITS2 sequences were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that with increasing forest-use intensity, local ( α -diversity) and total ( γ -diversity) species richness declined linearly, whereas species turnover between plots increased [18]. The forest-use intensity in the most intensively used plots led to sparse herb layer and reduced species richness [19].…”
Section: Introductionmentioning
confidence: 99%
“…The scale dependency of cross‐taxon congruence indicates that it is not advisable to use plants as a surrogate for foliar arthropod diversity beyond local scales (Schuldt et al. ).…”
Section: Discussionmentioning
confidence: 99%